On the Restoration of the Statue of Christ by J. H. Dannecker, from the Collection of the State Hermitage - Karcheva, Elena I.; Bogdanova, Aleksandra M.; Novikov, Andrei A. (Actual Problems of Theory and History of Art, 2018)
In 1954 a marble statue of Christ, the work by J. H. Dannecker (1758-1841), was transferred from the Chappelle in Aleksandrovsky Park of Pushkin city to the State Hermitage Museum. By that time, the statue had considerable damages that significantly changed its overall look and meaning. The disfigured art object could not be exhibited for both aesthetic and ethical reasons. In 2012 the restoration of the statue started: the main task for the specialists of the Laboratory for Stone Restoration of the State Hermitage Museum was to reconstruct numerous lost parts of the sculpture. Thanks to assembled iconographic materials and analogies of the sculpture, it became possible to create models of the lost parts. The choice of either traditional or contemporary methods for integrations depended upon the size of lacunas and the method of fixing the additions on the sculpture. The choice was also based on the decorative properties of restoration materials. It was decided to use marble, identical to the original marble of the statue, to recreate the largest and most significant lost parts (the hands). The smaller losses were substituted with composite materials including polyester resin, marble powder, and pigments. The application of different restoration materials and techniques presupposed by the condition of the preservation of the sculpture allowed us to return the exposition look to the famous artwork.